2011
DOI: 10.1038/npp.2011.254
|View full text |Cite
|
Sign up to set email alerts
|

Selective Blockade of Dopamine D3 Receptors Enhances while D2 Receptor Antagonism Impairs Social Novelty Discrimination and Novel Object Recognition in Rats: A Key Role for the Prefrontal Cortex

Abstract: Dopamine D(3) receptor antagonists exert pro-cognitive effects in both rodents and primates. Accordingly, this study compared the roles of dopamine D(3) vs D(2) receptors in social novelty discrimination (SND), which relies on olfactory cues, and novel object recognition (NOR), a visual-recognition task. The dopamine D(3) receptor antagonist, S33084 (0.04-0.63 mg/kg), caused a dose-related reversal of delay-dependent impairment in both SND and NOR procedures in adult rats. Furthermore, mice genetically deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(129 citation statements)
references
References 85 publications
7
122
0
Order By: Relevance
“…They also found that the deficit observed by blocking the VTA could be rescued by infusing the D1 receptor agonist SKF38397 into the mPFC. By using a similar microinjection approach in the mPFC we have also shown that blockade of dopamine D 3 receptors enhances, while D 3 receptor activation or antagonism of dopamine D 2 receptors impairs NOR in the rat (Watson et al 2012). Taken together these findings, which demonstrate the importance of dopamine neurotransmission in the mPFC for NOR consolidation, are also consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…They also found that the deficit observed by blocking the VTA could be rescued by infusing the D1 receptor agonist SKF38397 into the mPFC. By using a similar microinjection approach in the mPFC we have also shown that blockade of dopamine D 3 receptors enhances, while D 3 receptor activation or antagonism of dopamine D 2 receptors impairs NOR in the rat (Watson et al 2012). Taken together these findings, which demonstrate the importance of dopamine neurotransmission in the mPFC for NOR consolidation, are also consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…However, long term blockade of D2 receptors can lead to increased dopamine release and the activation of other dopamine receptors [52]. Thee higher availability of D3 receptors would thus be consistent with the observation that stimulation of D3 receptors impairs performance in the novel object test [53]. Furthermore, stimulation of D4 receptors was found to stimulate object exploration [54] as was observed in sulpiride-treated mice.…”
Section: Reducing Motivation For Exercise Has Limited Behavioural Impactsupporting
confidence: 78%
“…Thus, it is possible that loss of M 1 -mediated mLTD at the hippocampo-PFC synapse plays a major role in regulating PFC activation by hippocampal afferents under normal conditions, and that loss of this function contributes to the increased activation of the PFC and resultant behavioral outcomes of dysfunctional recognition memory and social interaction in this rodent model. As normal PFC function is essential for both social interaction (Elliott et al, 2012;Shah and Treit, 2003;Wall et al, 2012) and recognition memory (Bekinschtein and Weisstaub, 2014;Watson et al, 2012) in rodents, this study provides the first direct evidence for a potential role of impaired M 1 -mediated mLTD in PFC as an underlying cause of these behavioral deficits.…”
Section: Role Of M 1 Pam In Pcp-treated Micementioning
confidence: 70%